Rebolusyong 1896 [videorecording] totoo ban - Abaya, Marilou Diaz.; David, Randy; Millado, Ces.; ABC 5 (Television station : Quezon City, Philippines).; Public Forum (Television program). (Quezon City ABC 5, 1996)
A Public Forum episode on the fact of Revolution 1896 discussed by Randy David with professors/historians, Bro. Ambeth Ocampo, Dr. Vivencio Jose and Dr. Milagros Guerrero.
VHS.
Picture clippings during the revolution 1896 with 1 hr. running time.
Keywords: Philippines -- History -- Revolution, 1896-1898.